2013
DOI: 10.1038/ncomms3308
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic p53 inhibits Parkin-mediated mitophagy and promotes mitochondrial dysfunction in the mouse heart

Abstract: Cumulative evidence indicates that mitochondrial dysfunction has a role in heart failure progression, but whether mitochondrial quality control mechanisms are involved in the development of cardiac dysfunction remains unclear. Here we show that cytosolic p53 impairs autophagic degradation of damaged mitochondria and facilitates mitochondrial dysfunction and heart failure in mice. Prevalence and induction of mitochondrial autophagy is attenuated by senescence or doxorubicin treatment in vitro and in vivo. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
391
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(404 citation statements)
references
References 55 publications
9
391
1
3
Order By: Relevance
“…Consistently, p53 knockdown prevented the decrease in mitochondrial membrane potential and inhibited mitochondrial ROS accumulation. Our results are in line with previous studies that show that the p53‐parkin inhibition pathway plays an important role in cardiac ageing and drives age‐related diseases, such as heart failure and diabetes (Hoshino et al, 2014, 2013 ). Notably, we provide additional mechanistic evidence that p53 is a major mediator of the MAO‐A‐dependent response.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistently, p53 knockdown prevented the decrease in mitochondrial membrane potential and inhibited mitochondrial ROS accumulation. Our results are in line with previous studies that show that the p53‐parkin inhibition pathway plays an important role in cardiac ageing and drives age‐related diseases, such as heart failure and diabetes (Hoshino et al, 2014, 2013 ). Notably, we provide additional mechanistic evidence that p53 is a major mediator of the MAO‐A‐dependent response.…”
Section: Discussionsupporting
confidence: 93%
“…It is known that parkin translocation can be inhibited by interaction with cytosolic p53 (Hoshino et al, 2013). In H9C2 cells, we observed that Tyr treatment for 72 hr induced the accumulation of cytosolic p53 levels and increased p53‐parkin interaction (Figure 5a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we observed a decreased expression of NRF‐1 in fibroblasts from COPD patients treated with hemin, suggesting that another mechanism could be involved. Indeed, cytoplasmic p53, which accumulates in senescence, interacts with Parkin and prevents its translocation to dysfunctional mitochondria, thus suppressing mitophagy (Ahmad et al, 2015; Hoshino et al, 2013). Similarly, expression of PINK‐1 is low in aging lungs, which participate in the deletion of mitophagy (Bueno et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This leads to greater production of ROS and damage to mitochondrial proteins, lipids, and DNA which further activates innate immunity and chronic inflammation (Baroja‐Mazo et al ., 2014; Wu et al ., 2015). These processes contribute to cardiomyocyte dysfunction, which occurs with aging and could, in turn, lead to chronic inflammation, remodeling within the myocardium, and pathological left ventricular hypertrophy to exacerbate HF regardless of etiology (Tsutsui et al ., 2009; Hafner et al ., 2010; Hoshino et al ., 2013). As aging is linked to both frailty and HF, it is conceptually plausible that the impaired biological processes that lead to chronic inflammation serve as a common pathophysiological link between frailty and HF (Fig.…”
Section: How Aging Frailty and Hf Interact To Induce Inflammationmentioning
confidence: 99%
“…An experimental study found that defects in clearing defective mitochondria (i.e., a process termed mitophagy Lemasters, 2005) within the myocardium leads to mitochondrial dysfunction (Hoshino et al ., 2013). Furthermore, defective mitophagy within the myocardium leads to cell death and the release of mitochondrial DNA that activates Toll‐like receptor (TLR) 9 to induce myocardial inflammation, pressure overload, and cardiac hypertrophy leading to HF (Oka et al ., 2012).…”
Section: How Aging Frailty and Hf Interact To Induce Inflammationmentioning
confidence: 99%